QFD Application of the Quality Function Deployment (QFD) Method in Construction Projects: Systematic Literature Review: Quality Function Development - aditya brata; Cucu Suhara; Pahala R; Ray William; Humiras Hardi Purba; Hibarkah Kurnia (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
In the production sector, companies that have successfully applied concurrent engineering tools, including Quality Function Deployment (QFD) define customer requirements at the early stages of their design development. The purpose of this study is to determine the type of construction, country location, and year of research related to the application of the QFD method. This study uses the literature review method. Sources of articles were obtained and processed from National and International journals from 1999 to 2022. The number of similar articles identified was 45 articles. The results obtained from this study indicate that 15 research journals apply QFD to office building construction projects, and most research is carried out in 2017 while most research locations are carried out in Indonesia.